(Post-)Kemalism as a lived experience in public making-meydan - Nilüfer Göle (European Journal of Turkish Studies)
In this article, I explore debates on Kemalism and Post-Kemalism, not just as a nexus of ideas, but primarily as lived experiences. Lived experience (Erlebnis) intertwines biography and history, connecting personal subjectivities with collective experiences. Treating Kemalism and Post-Kemalism as lived experiences implies interconnections between personal and collective encounters, represented through language. After introducing Atatürkism and Kemalism, I discuss the Post-Kemalist moment in Turkey. While refraining from strictly labeling my work as "post-Kemalist," my involvement, as the author of "Modern Mahrem," becomes imperative. I defend the thesis that critiques of Kemalism, by challenging taboos and advocating dialogical voices, shape an inclusive public space in contemporary Turkey. This essay highlights blind spots in the Post-Kemalist debate, focusing on Muslim-secular dynamics, underrepresented voices, and Turkey's EU membership repercussions.